2019
DOI: 10.1016/bs.ircmb.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

T Cells and Regulated Cell Death

Abstract: Cell death plays two major complementary roles in T cell biology: mediating the removal of cells that are targeted by T cells and the removal of T cells themselves. T cells serve as major actors in the adaptive immune response, and function by selectively killing cells which are infected or dysfunctional. The selectivity in the T cell recognition and elimination is a highly regulated feature, which in itself involves the death of both autoreactive T cells and T cells which are unable to recognise threats. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 328 publications
(354 reference statements)
2
16
0
Order By: Relevance
“…Hypoxia prevents T and NK cell development and activation in animal models [42]. Our analysis showed that children with osteosarcoma at high risk of experiencing hypoxia had an elevated number of CD4 cells, suggesting an immunosuppressive disorder.…”
Section: Discussionmentioning
confidence: 61%
“…Hypoxia prevents T and NK cell development and activation in animal models [42]. Our analysis showed that children with osteosarcoma at high risk of experiencing hypoxia had an elevated number of CD4 cells, suggesting an immunosuppressive disorder.…”
Section: Discussionmentioning
confidence: 61%
“…By the intrinsic pathway of the mitochondria-dependent apoptosis, activation by the diflavonoid may be due to the fact that it is a stress promoter for the cell, which culminates in the mitochondrial outer membrane permeabilization (MOMP), allowing the release of proteins from the mitochondrial intermembrane space. This happens in T cells type II because the apoptotic signal needs to be amplified by caspases 3 and 7 [32,33]. In case the biflavonoid crosses the cell membrane, by active transport of K + /Na + pumps or even by the calcium–sodium ion exchanger, it can activate the signaling cascade of the binding with the Fas/CD95 receptor by the direct interaction of the biflavonoid with tBID through the R71 and S78 residues; however, BID (BH3 interacting-domain death agonist)is directly activated by caspase 8, generating a tBID, moving to the mitochondria to release cytochrome C (prior stimulation of the Bax–Bak complex, members of the pro-apoptotic Bcl-2 family) [32], to immediately form the caspase-9 Apaf1 complex, which activates caspase-6 and caspase-3 to induce apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Defective apoptosis of autoreactive effector T cells has been assumed to be a driving mechanism of autoimmunity [29, 30]. Thus, promotion of apoptosis of hyperactivated T cells is a key approach to the treatment of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%